223 READMISSION POST STROKE: RATES AND REASONS FOR READMISSION IN THE 18 MONTHS FOLLOWING HOSPITAL DISCHARGE. (25th October 2022) - Hobson, H; Cogan, N; Dunne, S; Collins, R; Ryan, D
Abstract: Background: The Irish healthcare system faces the same challenges presented to healthcare systems worldwide, ageing populations and the increasing disease burden from chronic conditions. There is a need to respond to and meet these challenges placed on an already pressurized healthcare systems originally set up to respond to acute, episodic care. It would be beneficial to review reasons for unplanned readmissions post stroke to examine whether these readmissions could be predicted, targeted and prevented and whether there are individuals who could be targeted for intervention post hospital discharge, to reduce readmission rates post stroke. Methods: Using data from the Hospital In-Patient Enquiry (HIPE) patients were identified who had been discharged with a primary diagnosis of stroke. Data was then examined to identify whether these patients had acute hospital readmissions in the 18-month period following discharge for stroke. Using HIPE and patient discharge letters we identified the reasons for these readmissions and categorized them accordingly. Results: A total of 224 live stroke discharges were identified from 2018. 77 patients were readmitted within 18 months of discharge. In total these 77 patients accounted for 139 admissions. Of the 77 patients that were readmitted average Length of Stay (LOS) was 19 days. Of the 77, 12 were due to recurrent stroke while 49 presented with a new complaint that fell into one of the following four categories, pneumonia, falls/fractures, dementia related, medical complications/medication related Conclusion: There is a need to identify the unmet needs of stroke patients post hospital discharge so as to reduce the number of readmissions. This would involve screening to identify those suitable to attend a specialist multidisciplinary six-month review clinic where these patients could have onward referral to the appropriate in hospital and community services including intensive dysphagia clinics, therapy-lead spasticity clinic, upper limb rehabilitation programmes, and medical social work support for unmet needs with links to the community.